Hepatotoxicity with antibody maytansinoid conjugates: A review of preclinical and clinical findings. Issue 5 (1st February 2018) - Taplin, Sarah; Vashisht, Kapil; Walles, Markus; Calise, David; Kluwe, William; Bouchard, Page; Johnson, Robert
Abstract: Maytansinoids, the potent cytotoxic derivatives of the alkaloid maytansine are used as payloads in antibody maytansinoid conjugates. This article reviews clinical and preclinical hepatotoxicity observed with antibody maytansinoid conjugates used to treat cancer. Specific aspects of drug distribution, metabolism and excretion that may impact hepatotoxicity are reviewed vis‐à‐vis the kind of maytansinoid in the conjugate, cleavable or non‐cleavable linkers, linker–payload combinations, drug to antibody ratio, metabolite formation, hepatic enzyme induction in relation to drug–drug interactions and species, age and gender differences. The article also sheds light on factors that may protect the liver from toxic insults. Abstract : This article reviews clinical and preclinical hepatotoxicity observed with antibody maytansinoid conjugates used to treat cancer. Specific aspects of drug distribution, metabolism and excretion that may impact hepatotoxicity are reviewed vis‐à‐vis the kind of maytansinoid in the conjugate, cleavable or non‐cleavable linkers, linker–payload combinations, drug to antibody ratio, metabolite formation, hepatic enzyme induction in relation to drug–drug interactions and species, age and gender differences. The article also sheds light on factors that may protect the liver from toxic insults.